The impact of a program based on the narrative approach to develop the skill of creative written expression among the students of the Institute of teaching Arabic language to non- native speakers at the Islamic University in Madinah - Al- otaib, Naif Ca'dan (Journal of Educational and Psychological Sciences, 2020)
The aim is to develop a list of written expression skills required for students, And to prepare a list of the foundations of building a program based on the narrative approach to develop the skill of creative written expression among students, build a program based on the skill of creative written expression required for students, and identify the impact of a program based on the story Creative expression of students). The researcher used the semi-experimental method to study the results of the tribal and post-test, as well as the analytical descriptive approach to the study of concepts and their development in the framework of the theoretical framework, which will be based on secondary data from scientific sources, such as books and periodicals. Data for the field study segment were analyzed through the Statistical Package for Social Sciences (SPSS) program, and percentages, computational averages, and T-test samples were extracted.After the researcher verified the validity of his tools and materials and measuring their stability, he began to apply them to the research sample consisting of (28) students of the fourth level in the Institute of Arabic Language Teaching non- speakers at the Islamic University in Medina, After the analysis, the researcher found the following results:- To find a list of creative written expression skills required for students. This list included six basic skills that resulted in thirty- one sub-skills.- The rate of availability of creative written expression skills among the students was (51.8) and this percentage is (weak) according to the Islamic University regulations.- The results showed the effect of the program based on the narrative approach in the development of creative written expression skills among the students. There were statistically significant differences at the level of (0.05) between the average of the students in the tribal and remote application in favor of the post-application.In light of the findings of the current research, some recommendations and proposals were presented.
Keywords: storytelling; creative written expression; language school students for non- native speakers; non- native speakers; native speakers